A randomized phase III trial of denosumab before curettage for giant cell tumor of bone. JCOG1610. (26th April 2022) - Urakawa, Hiroshi; Nagano, Akihito; Machida, Ryunosuke; Tanaka, Kazuhiro; Kataoka, Tomoko; Sekino, Yuta; Nishida, Yoshihiro; Takahashi, Mitsuru; Kunisada, Toshiyuki; Kawano, Masanori; Yoshida, Yukihiro; Takagi, Tatsuya; et al.
Abstract: Objectives: The aim of JCOG1610 (randomized controlled phase III trial) was to confirm the superiority of preoperative denosumab to curettage with adjuvant local therapy for patients with giant cell tumor of bone without possible post-operative large bone defect. Methods: The primary endpoint was relapse-free survival and the total sample size was set at 106 patients. Patient accrual began in October 2017. However, the accrual was terminated in December 2020 due to a recommendation from the Data and Safety Monitoring Committee because of poor patient accrual. Now, we report the descriptive results obtained in this study. Results: A total of 18 patients had been registered from 13 Japanese institutions at the time of termination on December 2020. Eleven patients were assigned to Arm A (curettage and adjuvant local therapy) and 7 to Arm B (preoperative denosumab, curettage and adjuvant local therapy). Median follow-up period was 1.6 (range: 0.5–2.8) years. Protocol treatment was completed in all but one patient in Arm A who had a pathological fracture before surgery. All patients in Arm B were treated with five courses of preoperative denosumab. Relapse-free survival proportions in Arm A and B were 90.0% (95% confidence interval: 47.3–98.5) and 100% (100–100) at 1 year, and 60.0% (19.0–85.5) and 62.5% (14.2–89.3) at 2 years, respectively [hazard ratio (95% confidence interval): 1.51 (0.24–9.41)]. Conclusion: In terms of relapse-free survival, the superiority of preoperative denosumab was not observed in patients with giant cell tumor of bone without possible post-operative large bone defect. Abstract : Though JCOG1610 gave only descriptive results, the superiority of preoperative denosumab was not observed in patients with giant cell tumor of bone without possible post-operative large bone defect in terms of relapse-free survival.